Boola's secrets - Bradbury, Pamela Zanin (New York : Little Simon, 1988)
Boola doesn't like to howl and spook like all the other little ghosts. Boola has many secrets, and the biggest secret, and the biggest secret of all is her new friendship with a young boy and his dog.
Keywords: Ghosts -- Fiction; Children stories